Basal Forebrain Atrophy Is Associated With Allocentric Navigation Deficits in Subjective Cognitive Decline - Chen, Qian; Wu, Sichu; Li, Xin; Sun, Yi; Chen, Wenqian; Lu, Jiaming; Zhang, Wen; Liu, Jiani; Qing, Zhao; Nedelska, Zuzana; Hort, Jakub; Zhang, Xin; et al. (Frontiers in Aging Neuroscience, 2021)
Individuals with subjective cognitive decline (SCD) are at higher risk of incipient Alzheimer’s disease (AD). Spatial navigation (SN) impairments in AD dementia and mild cognitive impairment patients have been well documented; however, studies investigating SN deficits in SCD subjects are still lacking. This study aimed to explore whether basal forebrain (BF) and entorhinal cortex (EC) atrophy contribute to spatial disorientation in the SCD stage. In total, 31 SCD subjects and 24 normal controls were enrolled and administered cognitive scales, a 2-dimensional computerized SN test, and structural magnetic resonance imaging (MRI) scanning. We computed the differences in navigation distance errors and volumes of BF subfields, EC, and hippocampus between the SCD and control groups. The correlations between MRI volumetry and navigation distance errors were also calculated. Compared with the controls, the SCD subjects performed worse in both egocentric and allocentric navigation. The SCD group showed volume reductions in the whole BF (p < 0.05, uncorrected) and the Ch4p subfield (p < 0.05, Bonferroni corrected), but comparable EC and hippocampal volumes with the controls. In the SCD cohort, the allocentric errors were negatively correlated with total BF (r = -0.625, p < 0.001), Ch4p (r = -0.625, p < 0.001), total EC (r = -0.423, p = 0.031), and left EC volumes (r = -0.442, p = 0.024), adjusting for age, gender, years of education, total intracranial volume, and hippocampal volume. This study demonstrates that SN deficits and BF atrophy may be promising indicators for the early detection of incipient AD patients. The reduced BF volume, especially in the Ch4p subfield, may serve as a structural basis for allocentric disorientation in SCD subjects independent of hippocampal atrophy. Our findings may have further implications for the preclinical diagnosis and intervention for potential AD patients.